NON-OPERATIVE TREATMENT OF GUNSHOT WOUNDS OF SOFT TISSUES - Khoroshun, E.M.; Makarov, V.V.; Nehoduiko, V.V.; Shypilov, S.A.; Tertyshnyi, S.V.; Veryovkin, I.V.; Vastyanov, R.S. (World of Medicine and Biology, 2024)
The purpose of the study was to analyze own experience of soft tissues gunshot wounds non-operative treatment. Clinical observations were performed on 829 wounded which were admitted to the Military Medical Clinical Centre of the Northern Region of the Command of the Medical Forces of the Armed Forces of Ukraine. All of the wounded were men. The wounded were randomized on 3 groups according to the needs for primary surgical treatment of the wound. All wounded received the same treatment. Foreign bodies (metal fragments) were partially removed with the help of a modern surgical magnetic tool. A third of all soft tissue gunshot wounds were proved do not require primary surgical treatment. The criteria for primary surgical treatment not performing are soft tissues gunshot wounds of small sizes, of different localization and number without signs of inflammation. Non-operative treatment of soft tissues gunshot wounds includes antibiotic prophylaxis, anti-tetanus toxoid administration, anesthesia, treatment of wounds with antiseptic solutions, aseptic wound dressings. Non-operative treatment of wounded with soft tissue gunshot wounds using the magnetic detection turned out to be highly effective in modern conditions for a significant number of people due to the acceleration of diagnostic process, treatment and recovery and due to entirely medical accompanying advantages.